Developing the Character of Learning Community at Madrasah Tsanawiyah in Bantul Yogyakarta: Islamic Education in Nusantara Perspective - Kamilati, Nurul; Sutrisno, Sutrisno; Sumardi, Yosaphat (ADDIN, 2019)
This research aims to promote the development of the character of  learning community at Madrasah Tsanawiyah of Bantul Regency Yogyakarta, and two problems posed to be addressed: why the character of community learning pattern does not realize as it has been expected,  and how does the development of the character of learning community  at MTs of Bantul look like? The research uses the Research and Development model that is consisted of four stages: exploration, development, tests, and dissemination. The data were collected by means of observatiosn, interviews, questionaire, and review of documentation. The results show: (1) the character of learning community  at the MTs in Bantul Regency has not been fully established because the teachers were not active in preparing their lesson study, and they did not benefit from it. Also, they were too busy in fulfilling their obligations as teachers; (2) the development of the character of learning  community at MTs in Bantul could be implemented through Classroom Action Research-based lesson study plans which are consisted of five stages: consolidation of lesson study concepts, explanation of Classroom Action Research as a form of scientific publication, planning, implementation of action, and reflection.